A Case of Concurrent MPO-/PR3-Negative ANCA-Associated Glomerulonephritis and Membranous Glomerulopathy - Yasuyuki Nakada; Nobuo Tsuboi; Yasuto Takahashi; Hiraku Yoshida; Yoriko Hara; Hideo Okonogi; Tetsuya Kawamura; Yoshihiro Arimura; Takashi Yokoo (Case Reports in Nephrology)
We report a case in which antineutrophil cytoplasmic antibody- (ANCA-) associated glomerulonephritis and membranous glomerulopathy (MGN) were detected concurrently. The patient showed rapidly progressive renal deterioration. A renal biopsy showed crescentic glomerulonephritis, together with marked thickening and spike and bubbling formations in the glomerular basement membranes. Indirect immunofluorescence examination of the patient’s neutrophils showed a perinuclear pattern. Enzyme-linked immunosorbent assays revealed that the ANCA in this case did not target myeloperoxidase (MPO) or proteinase 3 (PR3) but bactericidal-/permeability-increasing protein, elastase, and lysosome. The relationship between these two etiologically distinct entities, MPO-/PR3-negative ANCA-associated glomerulonephritis and MGN, remains unclear.